IMPLIKASI HUMOR DAN PERAN LAYANAN KARYAWAN GARIS DEPAN TERHADAP KEPUASAN PELANGGAN - Widya Mulyati; Robert Kristaung (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2017)
This study aims to examine the implications of humor and the role of front-line employee services to customer satisfaction. The effect of front-line service employees calculates the factor of service encounters. The service encounter factor becomes one of the decisive factors in the service industry, especially the banking industry, especially in the era of digitization as the interaction between employees and customers is still needed. The research design used is hypothesis testing between humour, front-line service employees, to customer satisfaction by service encounter. The sample of this research is supported by 150 workers consisting of teller, customer service, and head teller/customer service department who participate as the respondent in this research. This research uses SEM analysis. The result of this research supports the hypothesis that humor positively effects frontline service employees and front -line service employees affect the service encounter. This research fails to prove that service encounter has a significantly direct effect on customer satisfaction. Therefore, the implication of service encounter is still a crucial point for the banking industry in achieving customer satisfaction.